Genome analyses of the carboxydotrophic sulfate-reducers Desulfotomaculum nigrificans and Desulfotomaculum carboxydivorans and reclassification of Desulfotomaculum caboxydivorans as a later synonym of Desulfotomaculum nigrificans. Issue 3 (November 2014) - Visser, Michael; Parshina, Sofiya; Alves, Joana; Sousa, Diana; Pereira, Inês; Muyzer, Gerard; Kuever, Jan; Lebedinsky, Alexander; Koehorst, Jasper; Worm, Petra; Plugge, Caroline; Schaap, Peter; et al.
Abstract Desulfotomaculum nigrificans andD. carboxydivorans are moderately thermophilic members of the polyphyletic spore-forming genusDesulfotomaculum in the familyPeptococcaceae . They are phylogenetically very closely related and belong to 'subgroup a' of theDesulfotomaculum cluster 1.D. nigrificans andD. carboxydivorans have a similar growth substrate spectrum; they can grow with glucose and fructose as electron donors in the presence of sulfate. Additionally, both species are able to ferment fructose, although fermentation of glucose is only reported forD. carboxydivorans .D. nigrificans is able to grow with 20% carbon monoxide (CO) coupled to sulfate reduction, whileD. carboxydivorans can grow at 100% CO with and without sulfate. Hydrogen is produced during growth with CO byD. carboxydivorans . Here we present a summary of the features ofD. nigrificans andD. carboxydivorans together with the description of the complete genome sequencing and annotation of both strains. Moreover, we compared the genomes of both strains to reveal their differences. This comparison led us to propose a reclassification ofD. carboxydivorans as a later heterotypic synonym ofD. nigrificans .